Sensory and control system for smart fan - Rahman, Md. Mozasser; Zakaria, Mohd Fahrul Radzi; Sidek, Shahrul Na'im (ICROS and KIEE, 2015)
A smart fan is a development of an ordinary fan that consists of several features to help more comfortable and easier life. Ordinary stand fan is operated manually which people has to determine the speed of the fan and the oscillation of the fan is fix at a certain degrees. The smart fan is developed to have a speed regarding to the environment temperature and it will only operate as there is presence of human. Furthermore the fan is designed to oscillate with respect to the human location. To this extend, researches on the temperature controller and human location detection have been done and the system design explained in this report. The working principle of smart fan is interrelated between electromechanical, electronics and control system. The LM35 is used to determine the environment temperature meanwhile the passive infrared is used to determine the presence of human and ultrasonic sensors are used to detect the human location. The system is controlled by microcontroller which making the typical stand fan to be smarter.